Polyhedral high-temperature pouring highlight grinding block and preparation method thereof

By optimizing material ratio and process conditions, the high-gloss grinding blocks are prepared by using polyhedral high-temperature casting process, which solves the problems of insufficient wear resistance and mechanical strength of traditional grinding blocks in high-temperature environments, and achieves higher performance indicators and stability.

CN119734210APending Publication Date: 2025-04-01FOSHAN ZHONG YI YUAN DA ELECTRIACAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411878471.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Traditional powder hot-pressed grinding blocks have problems such as insufficient wear resistance, low mechanical strength, low polishing luminosity and unstable photometry, especially in high temperature environments, these defects are more significant.

Method used

By optimizing the material ratio, a high-temperature casting process of polyhedron is adopted, using adhesives, reinforcers, superhard materials, tougheners and hollow materials, combined with precise control of vacuum degree, pressurization pressure and heating temperature, a high-performance polyhedron high-temperature casting high-gloss grinding block is prepared.

Benefits of technology

The better wear resistance, mechanical strength, dimensional accuracy, geometric shape stability and polishing photometric stability of the grinding block are achieved, which significantly improves the overall performance of the grinding block.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119734210A_ABST
    Figure CN119734210A_ABST
Patent Text Reader

Abstract

The invention discloses a polyhedral high-temperature pouring highlight grinding block and a preparation method thereof.The preparation method comprises the steps that an adhesive, a reinforcing agent, a superhard material, a toughening agent and an air making material which serve as raw materials are suspended and stirred according to a preset proportion at normal temperature and normal pressure, and a premix is prepared; adding the premix into a polyhedral high-temperature pouring highlight grinding block mold, covering the mold with a hook-shaped magic tape, and then sealing and vacuumizing the mold; the sealed and vacuumized mold is pressurized and heated, and the polyhedral high-temperature pouring highlight grinding block tool bit is obtained; and the polyhedral high-temperature pouring highlight grinding block tool bit, a rubber spring washer and an ABS clamping plate are bonded and subjected to constant pressure forming, and the polyhedral high-temperature pouring highlight grinding block is obtained. Compared with a traditional powder hot-pressing grinding block, the high-gloss grinding block prepared by the invention has the characteristics of better wear resistance, mechanical strength, dimensional accuracy, geometric shape stability, polishing luminosity stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of abrasive tool manufacturing, and in particular relates to a polyhedron high-temperature cast high-gloss abrasive block and a preparation method thereof. Background Art

[0002] Traditional powder hot-pressed grinding blocks usually have some defects, such as insufficient wear resistance, low mechanical strength, low polishing brightness and unstable brightness. These problems are often caused by improper material ratio or unreasonable preparation process. These defects are particularly significant for grinding blocks in high-temperature application environments, because high temperature conditions will aggravate the aging and wear of materials. Therefore, it is necessary to develop a new type of polyhedral high-temperature cast high-gloss grinding block and its preparation method. Summary of the invention

[0003] In view of the deficiencies in the prior art, the purpose of the present disclosure is to provide a polyhedron high-temperature cast high-gloss grinding block and a preparation method thereof, which aims to solve the problems of insufficient wear resistance, low mechanical strength, low polishing degree and unstable polishing brightness of the grinding block.

[0004] To achieve the above objectives, the present disclosure provides the following technical solutions: A polyhedral high-temperature cast high-gloss grinding block, the components of which include an adhesive, a reinforcing agent, a superhard material, a toughening agent and a hollowing material, wherein the mass percentages of the adhesive, the reinforcing agent, the superhard material, the toughening agent and the hollowing material are 5% to 15%, 1% to 10%, 70% to 80%, 1% to 5% and 0 to 5%, respectively.

[0005] The present disclosure also provides a method for preparing a polyhedron high-temperature cast high-gloss grinding block, comprising the following steps: suspending and stirring an adhesive, a reinforcing agent, a superhard material, a toughening agent and a hollowing material as raw materials in a preset proportion at room temperature and pressure to prepare a premix; adding the premix to a polyhedron high-temperature cast high-gloss grinding block mold, covering the surface of the premix with hook-type Velcro, and then sealing and evacuating the mold; pressurizing and heating the sealed and evacuated mold to obtain a polyhedron high-temperature cast high-gloss grinding block head; bonding the polyhedron high-temperature cast high-gloss grinding block head to a rubber spring pad and an ABS card board, and forming them under constant pressure to obtain a polyhedron high-temperature cast high-gloss grinding block.

[0006] Optionally, the adhesive includes any one of the following: fiberglass resin, epoxy resin, unsaturated polyester resin, phenolic resin, polyurethane resin and silicone resin.

[0007] Optionally, the reinforcing agent includes any one of the following: calcium sulfate whisker, silicon carbide whisker, silica lime whisker, silicon nitride whisker and aluminum oxide whisker.

[0008] Optionally, the superhard material includes any one of the following: artificial diamond, silicon carbide, aluminum oxide, cubic boron nitride and zirconium dioxide.

[0009] Optionally, the pore-forming material includes any one of the following: sodium chloride, anhydrous sodium sulfate, sodium sulfate, sucrose pellets and baking soda.

[0010] Optionally, the raw material also includes polishing powder.

[0011] Optionally, the mold is evacuated to -0.01 MPa to -0.1 MPa. Optionally, the pressure applied to the sealed and vacuumed mold is 1000 MPa to 1900 MPa.

[0012] Optionally, the heating temperature of the sealed and vacuumed mold is 80° C. to 180° C.

[0013] Compared with the prior art, the present invention has the following beneficial effects: The present invention achieves high-performance preparation of polyhedron high-temperature cast high-gloss abrasive blocks by optimizing material ratios, accurately controlling vacuum degree, pressurization pressure and heating temperature. Compared with traditional powder hot-pressed abrasive blocks, the abrasive blocks prepared by the method described in the present invention have better wear resistance, mechanical strength, dimensional accuracy, geometric shape stability and polishing brightness stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic flow chart of a method for preparing a polyhedral high-temperature cast high-gloss abrasive block provided by an embodiment of the present disclosure. DETAILED DESCRIPTION

[0015] The following will refer to the attached Figure 1 Specific embodiments of the present disclosure are described in detail. Although specific embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.

[0016] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present disclosure, but the description is based on the general principles of the specification and is not used to limit the scope of the present disclosure. The scope of protection of the present disclosure shall be determined by the attached claims.

[0017] To facilitate understanding of the embodiments of the present disclosure, further explanation will be given below using specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present disclosure.

[0018] In one embodiment, the present disclosure provides a polyhedron high-temperature cast high-polish grinding block, the components of which include an adhesive, a reinforcing agent, a superhard material, a toughening agent, and a hollowing material, wherein the mass percentages of the adhesive, reinforcing agent, superhard material, toughening agent, and hollowing material are 5% to 15%, 1% to 10%, 70% to 80%, 1% to 5%, and 0 to 5%, respectively.

[0019] The mass percentages of the above raw materials are the best ratios obtained by the present disclosure after multiple tests. Below, the present disclosure explains in detail why the above ratios are selected as the best ratios: Exemplarily, if the ratio of the adhesive is too high, for example, the ratio is 20%, it is found that the abrasive block prepared by this ratio will become soft, resulting in a decrease in grinding efficiency, and the durability of the abrasive block will also be affected, because the adhesive itself does not have a very high wear resistance, so if the ratio is too large, the mechanical properties of the abrasive block will be reduced. In addition, too much adhesive will occupy the space that should be occupied by the superhard material, thereby reducing the grinding efficiency of the abrasive block. In addition, if the ratio of the adhesive is too low, for example, the ratio is 3%, it is found that the abrasive block prepared by this ratio is easy to break, because too little adhesive will lead to insufficient bonding between other materials, thereby affecting the mechanical strength and durability of the abrasive block.

[0020] For example, if the ratio of the reinforcing agent is too high, for example, the ratio is 15%, it is found that the grinding block prepared by this ratio is prone to brittle fracture during use, because too much reinforcing agent will increase the brittleness and reduce the toughness of the grinding block, so that the grinding block is prone to fracture during use. In addition, if the ratio of the reinforcing agent is too low, for example, the ratio is 0.5%, the mechanical strength of the grinding block prepared by this ratio is difficult to meet the requirements, because less reinforcing agent cannot effectively disperse stress, bridge cracks or deflect cracks, making cracks more likely to expand, thereby reducing the mechanical strength of the grinding block.

[0021] Exemplarily, if the ratio of the superhard material is too high, for example, the ratio is 85%, it is found that the grinding block made by this ratio is easy to break and the mechanical strength will also decrease, because too much superhard material means that the ratio of adhesive and reinforcing agent will decrease, wherein the reduction of the adhesive ratio will cause the superhard material particles to have insufficient bonding force and fall off easily, and the reduction of the reinforcing agent ratio means that the amount of reinforcing agent is not enough to effectively improve the overall mechanical strength of the grinding block. In summary, if the ratio of superhard material is too high, the ratio of adhesive and reinforcing agent will decrease, which will cause the structural stability of the grinding block to decrease, and the decrease in structural stability will cause the grinding block to be prone to cracks or delamination during use. In addition, if the ratio of superhard material is too low, for example, the ratio is 65%, this ratio means that the amount of superhard material is insufficient, so that the effective contact area available for grinding in the superhard material will be reduced, and during the grinding process, the roughness of the grinding surface will increase, which will cause the grinding efficiency and grinding quality of the superhard material to decrease.

[0022] For example, if the proportion of the toughening agent is too high, for example, the proportion is 7%, it is found that the grinding block made by this proportion will become softer, resulting in a decrease in grinding efficiency and wear resistance, because when the proportion of the toughening agent is too high, it will occupy the space that should be occupied by harder components (such as superhard materials), thereby reducing the proportion of hard components. If the proportion of the toughening agent is too low, for example, the proportion is 0.5%, it is found that the grinding block made by this proportion is more likely to suffer brittle fracture during use, because the proportion of the toughening agent is too low, the toughness of the grinding block will be reduced, so that the impact resistance of the grinding block when it is impacted by external force is reduced, and it is more likely to be damaged.

[0023] Exemplarily, hollowing materials are usually used to form pores in grinding blocks to improve certain properties of the grinding blocks, such as cutting efficiency and heat dissipation. However, if the proportion of hollowing materials is too high, for example, the proportion is 6%, it has been tested that the porosity inside the grinding block made by this proportion will increase significantly, resulting in a decrease in structural strength. When the grinding block is subjected to external forces, these pores may become stress concentration points, increasing the risk of the grinding block breaking. In addition, an excessively high proportion of hollowing materials will also cause uneven shrinkage or deformation of the grinding block during the preparation process, especially during the pressurized and heated treatment stage, thereby affecting the dimensional accuracy and geometric stability of the grinding block.

[0024] It should be noted that the present invention has conducted further experiments within the proportion range of each component determined above, and combined and tested the specific values ​​within the above mass ratio range through a series of technical means, including wear resistance test, mechanical strength test, toughness test, hardness test and density test.

[0025] Among them, the wear resistance test is carried out by Taber wear test (the wear resistance is evaluated by rubbing the sample under fixed conditions by rotating the grinding wheel and measuring the weight loss of the sample); the mechanical strength test is carried out by three-point bending test (the sample is placed on two supports and load is applied thereon until the sample breaks, and the mechanical strength is evaluated by calculating the maximum load); the toughness test is carried out by Charpy impact test (impact test is carried out by using a grinding block with a notch to evaluate the toughness of the sample when subjected to impact load); the hardness test is carried out by Rockwell hardness test (hardness is evaluated by measuring the depth of penetration of the indenter applied under standard conditions into the sample); the density test is carried out by water displacement method (density is calculated by measuring the weight loss of the sample in water).

[0026] Each of the above tests was performed at least three times, and this embodiment selected three optimal ratios for comparison and explanation: When the mass percentages of adhesive, reinforcing agent, superhard material and toughening agent are 8%, 4%, 78%, 4% and 2% respectively, the performance indicators of the grinding block are as follows: Wear resistance: weight loss is about 0.02g / 1000 revolutions Mechanical strength: The maximum load that can be sustained is about 1500 Newtons Toughness: Energy absorbed is about 30 joules Hardness: about 60 HR Density: about 2.65g / cubic centimeter When the mass percentages of adhesive, reinforcing agent, superhard material and toughening agent are 12%, 6%, 75%, 6% and 1% respectively, the performance indicators of the grinding block are as follows: Wear resistance: weight loss is about 0.03g / 1000 revolutions Mechanical strength: The maximum load that can be sustained is about 1400 Newtons Toughness: Energy absorbed is about 28 joules Hardness: about 58 HR Density: about 2.6g / cubic centimeter When the mass percentages of adhesive, reinforcing agent, superhard material and toughening agent are 11%, 7%, 70%, 7% and 5% respectively, the performance indicators of the grinding block are as follows: Wear resistance: weight loss is about 0.04g / 1000 revolutions Mechanical strength: The maximum load that can be sustained is about 1300 Newtons Toughness: Energy absorbed is about 26 joules Hardness: about 56 HR Density: about 2.55g / cubic centimeter Based on the above data, it is not difficult to conclude that when the mass percentages of adhesive, reinforcing agent, superhard material and toughening agent are 8%, 4%, 78%, 4% and 2% respectively, the performance indicators of the grinding block are all optimal. Therefore, this embodiment uses this ratio as the optimal ratio for preparing the high-light module. In another exemplary embodiment, Figure 1 As shown, the present disclosure also provides a method for preparing a polyhedral high-temperature cast high-gloss grinding block, comprising the following steps: S100: Suspending and stirring the adhesive, reinforcing agent, superhard material, toughening agent and hollowing material as raw materials in a preset ratio (i.e., the ratio described in the previous embodiment) at room temperature and pressure to prepare a premix; S200: adding the premix into a polyhedron high-temperature casting high-gloss abrasive block mold, covering the surface of the premix with hook-shaped Velcro, and then sealing and vacuumizing the mold; S300: Pressurizing and heating the sealed and vacuumed mold to obtain a polyhedron high-temperature cast high-gloss grinding block cutter head; S400: bonding the polyhedron high temperature cast high gloss grinding block head, the rubber spring pad and the ABS card board, and forming them by constant pressure to obtain a polyhedron high temperature cast high gloss grinding block.

[0027] In another exemplary embodiment, in step S100, the process of suspending and stirring the adhesive, reinforcing agent, superhard material, toughening agent and hollowing material as raw materials at a preset ratio at room temperature and pressure includes the following steps: S101: pretreating the adhesive, reinforcing agent, superhard material, toughening agent and hollowing material; In this step, pre-treating the adhesive includes placing the adhesive in a suitable container, adding an appropriate amount of solvent (such as water, alcohol or other organic solvents) as needed, heating the mixture mixed with the adhesive to a specified temperature (usually 40°C-60°C) using a gentle heating method (such as water bath heating), and slowly stirring until it is completely dissolved or a stable emulsion is formed.

[0028] The pretreatment of the reinforcing agent includes: grinding the reinforcing agent at a low intensity by using a ball mill or a vibration mill to make its surface rougher, so as to increase its contact area with other components and mechanical interlocking ability.

[0029] Pre-treatment of the superhard material includes: Due to the wide distribution of superhard material particle sizes, direct use will result in uneven mixing. Therefore, the superhard material needs to be graded by screening equipment first, specifically: use a standard sieve (such as 100 mesh, 200 mesh, etc.) to screen the superhard material, collect the powder within the target particle size range, and further finely grade the screened powder through an airflow classifier to ensure a narrow and uniform particle size distribution.

[0030] Pre-treating the toughening agent includes: adding the toughening agent to a small amount of pre-dissolved adhesive solution, and using a high-speed shear mixer or an ultrasonic disperser to vigorously disperse until a stable and uniform suspension is formed. Some toughening agents may easily agglomerate, which will affect their uniform distribution in the mixture. Therefore, pre-dispersing the toughening agent in the adhesive solution can avoid this problem.

[0031] The pretreatment of the pore-forming material includes: using a screen of appropriate specifications to remove larger particles or fine powder in the pore-forming material, then washing the pore-forming material after removing the larger particles or fine powder with water, and then drying it for standby use.

[0032] S102: adding and premixing the pretreated adhesive, reinforcing agent, superhard material, toughening agent and hollowing material in stages; In this step, a portion of the pretreated adhesive is first added, and low-speed stirring is started to allow the adhesive to be initially dispersed. The remaining adhesive and other pretreated ingredients are then added one by one. After each addition of new materials, a short but efficient premixing is immediately performed (for example, using a stirring blade with high shear force to stir, which can generate strong turbulence in a short time, promoting collision and dispersion between particles), thereby ensuring that the newly added ingredients can quickly blend with the existing mixture to avoid local concentrations that are too high or too low.

[0033] It should be noted that if the pre-treated adhesive, reinforcing agent, superhard material, toughening agent and hollowing material are added at once, the concentration in some areas will be too high or too low, while adding in stages can gradually control the proportion of each material, so that they have enough time to fully blend with the existing mixture, thereby achieving a more uniform distribution. In addition, since different materials have different physical properties (such as density, particle size, fluidity, etc.), by adding in stages, the mixing parameters (such as stirring speed, time) can be adjusted according to the specific needs of each component, thereby ensuring that each component can be optimally processed.

[0034] S103: Stir the premixed adhesive, reinforcing agent, superhard material, toughening agent and hollowing material, and during the stirring process, use online monitoring equipment (such as a viscometer or other suitable sensors) to continuously monitor the state changes of the materials, and adjust the stirring speed, time and intensity based on the monitoring data. For example, when a significant increase in viscosity is detected, reduce the stirring speed to prevent excessive shearing; when a trend of insufficient mixing is found, appropriately increase the stirring speed or extend the stirring time.

[0035] It should be noted that the present application introduces a pulse stirring mode, that is, rapid stirring for a period of time and then pausing for a moment before continuing. For example, it can be set to pause for 1 minute every 5 minutes of stirring, during which the particles are allowed to rearrange, and then high-speed stirring can be started again. When it is confirmed that all ingredients have been evenly distributed, the stirring is stopped, and the premix can be obtained at this time. Traditional continuous stirring may cause some fine particles (such as superhard materials, reinforcing agents) to attract each other and form agglomerates. Pulse stirring allows these particles to rearrange and disperse by periodically stopping stirring, thereby effectively reducing agglomeration. After each stirring pause, the particles in the material will temporarily lose the externally applied shear force and have the opportunity to naturally settle or float according to their own gravity or buoyancy. When the stirring is started again, these particles are more easily dispersed into the entire system, thereby achieving a more uniform distribution. In addition, pulse stirring can generate strong turbulence and shear force in a short time, causing more intense collision and friction between particles, accelerating the micro-mixing process between components, and helping to further break up larger particles into smaller units, thereby improving the uniformity of overall mixing. Compared with long-term continuous stirring, pulse stirring can achieve similar or even better mixing effects in a shorter time, while reducing unnecessary energy consumption and improving energy utilization. Furthermore, continuous stirring can easily draw outside air into the material, forming bubbles that are difficult to remove. Pulse stirring reduces the chance of air entering the material by periodically stopping stirring, and gives the already mixed air more time to escape from the surface of the material, thereby significantly reducing the bubble content in the finished product, thereby ensuring the density and mechanical strength of the final product.

[0036] In another exemplary embodiment, the adhesive includes any one of the following: fiberglass resin, epoxy resin, unsaturated polyester resin, phenolic resin, polyurethane resin and silicone resin.

[0037] Among the above adhesives, the pencil hardness of glass fiber reinforced plastic resin is 2H to 6B, the pencil hardness of unsaturated polyester resin is 2H to 6B, the pencil hardness of phenolic resin is 1H, the pencil hardness of polyurethane resin is 5-7H, the pencil hardness of epoxy resin is 4-5H, and the pencil hardness of silicone resin is HB or lower. It can be seen that among the above resin materials, polyurethane resin has the highest pencil hardness, indicating that it has the highest wear resistance, which means that it can withstand the scratches of harder objects without being easily damaged, thereby being able to extend the service life of the high-gloss grinding block. In addition, polyurethane resin has the best bonding ability (polyurethane resin is composed of hard segments and soft segments. This special molecular structure gives it the characteristics of being both tough and elastic. The hard segment provides good mechanical strength and chemical resistance, while the soft segment gives it elasticity. This unique structure enables polyurethane to form strong cohesive force and interaction force with the surfaces of various substrates, thereby achieving efficient bonding; in addition, the polar groups contained in the polyurethane adhesive, such as amino bonds, pulse bonds, ionic bonds, etc., can form Coulomb forces, van der Waals forces and hydrogen bonds with the surface of the substrate. Some NCO-terminated polyurethane adhesives can also react with moisture on the surface of the substrate to form chemical bonds, further enhancing the bonding force. This shows that the polyurethane resin forms a strong physical and chemical bond with the adherend at the molecular level.), can firmly bond various superhard materials (such as artificial diamond, silicon carbide, etc.) to the substrate, thereby ensuring the overall structural strength of the grinding block. Therefore, this embodiment preferably uses polyurethane resin as an adhesive for preparing high-gloss grinding blocks.

[0038] In another exemplary embodiment, the reinforcing agent includes any one of the following: calcium sulfate whiskers, silicon carbide whiskers, silicate lime whiskers, silicon nitride whiskers and aluminum oxide whiskers.

[0039] In this embodiment, among the above-mentioned several reinforcing agents, the silicon carbide whiskers and silicon nitride whiskers generally have higher hardness and heat resistance, and therefore are very suitable for applications requiring high strength and wear resistance. In particular, silicon carbide whiskers, because of their very high hardness and mechanical strength, can significantly improve the wear resistance and impact resistance of composite materials. In addition, silicon carbide whiskers also have excellent heat resistance, and their structure can maintain integrity and mechanical properties in high temperature environments. Furthermore, silicon carbide whiskers can form a strong bond with polyurethane resin (silicon carbide whiskers have higher hardness and strength, and can be embedded in a polyurethane resin matrix on the basis of using a coupling agent, thereby forming a physical mechanical interlocking structure. This interlocking structure helps to disperse stress and prevent crack propagation, thereby improving the overall performance of the composite material), thereby ensuring the overall structural strength of the grinding block.

[0040] In another embodiment, the superhard material includes any one of the following: artificial diamond, silicon carbide, aluminum oxide, cubic boron nitride and zirconium dioxide.

[0041] In this embodiment, the selection of superhard materials needs to be well matched with the adhesive (such as the preferred polyurethane resin) to ensure the overall structural strength of the grinding block. For example, if polyurethane resin is preferred as the adhesive, the selection of superhard materials should also consider whether it can form a good combination with the polyurethane resin. The purpose of this embodiment is to make a high-gloss grinding block that can work at high temperatures, so it is necessary to select a superhard material with good high-temperature resistance, such as artificial diamond or cubic boron nitride. Among them, since artificial diamond has high hardness (Mohs hardness is close to 10) and extremely high wear resistance, it can provide very high grinding accuracy and surface finish. Therefore, this embodiment uses artificial diamond as the optimal superhard material for preparing high-gloss grinding blocks.

[0042] In another embodiment, the pore-forming material includes any one of the following: sodium chloride, anhydrous sodium sulfate, sodium sulfate, sucrose pellets and baking soda.

[0043] In this embodiment, among the above materials, sodium chloride has good solubility in water, which means that in the process of preparing the grinding block, the sodium chloride particles can be easily removed by a water-soluble method, thereby forming a uniform pore structure inside the grinding block. An appropriate proportion of sodium chloride as a pore-forming material can improve the cutting efficiency and heat dissipation of the grinding block without significantly reducing the mechanical strength and wear resistance of the grinding block. By precisely controlling the amount and porosity of sodium chloride, a grinding block with excellent performance can be obtained. In addition, sodium chloride is non-toxic and harmless, easy to handle and recycle, and meets environmental protection requirements. Therefore, taking into account various factors such as solubility and the impact on the performance of the grinding block, this embodiment selects sodium chloride as the optimal pore-forming material for preparing high-gloss grinding blocks.

[0044] In another embodiment, the raw material further includes polishing powder.

[0045] In this embodiment, the polishing powder includes but is not limited to aluminum oxide, silicon dioxide, diamond powder, etc. By adding polishing powder, the surface finish of the final grinding block can be improved to achieve a higher polishing degree. In addition, the use of polishing powder can further improve the wear resistance of the grinding block and improve the surface quality of the grinding block, thereby reducing the surface defects of the grinding block and further increasing the service life of the grinding block.

[0046] In another exemplary embodiment, the mold is evacuated to a pressure of -0.01 MPa to -0.1 MPa.

[0047] In this embodiment, the purpose of evacuating the mold is to remove air in the premix, so as to avoid bubbles in the premix during the subsequent heating and curing process, thereby affecting the quality and performance of the high-gloss abrasive block.

[0048] According to the specific production practice, the best choice is to set the pressure range of mold vacuuming to -0.01MPa to -0.1MPa. Within this vacuum range, not only can the air in the premix be effectively removed, but also the density of the material during the casting process can be ensured. In the process of preparing the grinding block, if the pressure of the mold vacuuming is lower than -0.01MPa, that is, the vacuum degree is not enough, the gas in the premix cannot be effectively removed, and bubbles appear in the high-gloss grinding block finally prepared, affecting the product quality. In addition, if the vacuum pressure is higher than -0.1MPa, that is, the vacuum degree is too high, the premix will be deformed and the physical properties will change. For example, the adhesive in the premix will solidify prematurely, causing its viscosity to increase rapidly, thereby affecting its fluidity and distribution uniformity in the mold, and then affecting the structural integrity and performance of the product; in addition, the premature solidification of the adhesive will also lead to the formation of insufficiently mixed areas in the premix, causing internal defects such as pores or cracks, which will reduce the mechanical strength and durability of the high-gloss grinding block. Furthermore, too high a vacuum will also cause the volatile components in the premix (such as low molecular weight polymer segments and plasticizers and water in the premix) to evaporate too quickly, leaving bubbles in the adhesive, which will become permanent cavities after curing, thus affecting the appearance and mechanical properties of the high-gloss abrasive block. Furthermore, if the vacuum pressure is too high, not only will more advanced vacuum equipment be required, resulting in increased production costs, but also too high a vacuum degree will take longer to achieve, resulting in a longer processing cycle, thereby reducing production efficiency.

[0049] In summary, controlling the vacuum within the pressure range of -0.01MPa to -0.1MPa can basically balance the above-mentioned undesirable factors to ensure that the adhesive can be evenly distributed and reduce the formation of bubbles, while avoiding problems caused by too rapid volatilization, thereby ensuring that the final prepared high-gloss abrasive block meets the quality requirements.

[0050] It should be noted that the present disclosure further tested the premix based on the vacuum shaft in the above pressure range by using transmitted light detection and professional bubble detection equipment, and found that when the vacuum degree is -0.05MPa, the amount of bubbles in the adhesive is the least. At the same time, the present disclosure analyzed and detected the volatile components in the premix by using headspace solid phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS) analysis, and found that when the vacuum degree is -0.05 MPa, the volatile components in the mixture are most stable. Based on the above test results, the present disclosure prefers -0.05MPa as the optimal vacuum pressure value for the mold.

[0051] In another exemplary embodiment, the pressure applied to the sealed and vacuumed mold is 1000 MPa to 1900 MPa.

[0052] In this embodiment, multiple pressure values ​​are selected to pressurize the vacuumed mold, and the high-gloss grinding blocks obtained based on different pressure values ​​are tested. The test results show that when the pressurization pressure of the mold is lower than 1000MPa (for example, 900MPa), the mechanical strength and durability of the prepared high-gloss grinding blocks are difficult to meet the predetermined requirements. After analysis, the reason is that due to the low pressurization pressure, the premix is ​​difficult to be completely compacted, resulting in pores inside the finally prepared high-gloss grinding blocks. The presence of pores will reduce the density of the grinding block, and a lower density usually means lower mechanical strength and poorer durability. In addition, when the pressurization pressure of the mold is higher than 1900MPa (for example, 2000MPa), the dimensional accuracy and geometric shape of the prepared high-gloss grinding blocks do not meet the requirements. The reason is that the excessively high pressure causes the premix to undergo plastic deformation during the pressurization process. The plastic deformation will change the size and shape of the grinding block, such as twisting and bending, causing it to deviate from the design specifications, thereby affecting the quality of the grinding block. Therefore, in this embodiment, the pressurization pressure is set to 1000 MPa to 1900 MPa based on comprehensive consideration of the above factors. Within this pressure range, the premix can be compacted and the size and shape of the grinding block can meet the design specifications.

[0053] Below, this embodiment uses specific data to explain in detail the selection of the above-mentioned pressurization pressure range, as shown in Table 1: Table 1 The predetermined requirements of the grinding block of this embodiment are: mechanical strength: at least 1400 Newtons; durability: after 10,000 grinding cycles, the weight loss does not exceed 0.08g; density: at least 2.6g / cm3; dimensional accuracy: deviation ±0.05 mm; geometric shape: meet the design specifications. As can be seen from Table 1, when the pressurization pressure of the mold is 900 MPa, the mechanical strength, durability and density of the prepared high-light grinding block will be affected, because the premix is ​​not fully compacted, resulting in more pores inside. On the contrary, when the pressurization pressure is 1000 MPa, all performance indicators meet the predetermined requirements. When the pressurization pressure is 1900 MPa, the performance indicators are further improved, but still maintain good dimensional accuracy and geometric shape. When the pressurization pressure is 2000 MPa, although the mechanical strength, durability and density still meet the requirements, the dimensional accuracy and geometric shape of the grinding block do not meet the requirements due to plastic deformation of the premix. Therefore, this embodiment selects 1000MPa to 1900MPa as the pressure range for preparing high-gloss grinding blocks. This pressure range can ensure that the premix is ​​compacted and that the size and shape of the grinding blocks meet the design specifications, thereby achieving optimal mechanical strength and durability. It should also be noted that within the set pressure range of 1000MPa to 1900MPa, the applicant conducted further verification and found that, compared with other pressurization pressures, when the pressurization pressure was 1200MPa, the prepared grinding block had the best mechanical strength and durability (mechanical strength could reach 1550 Newtons, and the weight loss was 0.05g after 10,000 grinding cycles). In addition, under this pressure, the size and geometry of the grinding block also best met the design standards (deviation ±0.03 mm).

[0054] In summary, the present invention selects 1200MPa as the optimal value, which can ensure that the premix is ​​fully compacted, thereby maximizing the density and mechanical strength of the grinding block, while ensuring that the dimensional accuracy and geometric shape of the grinding block best meet the design requirements, which is helpful to prepare a polyhedron high-temperature cast high-gloss grinding block with optimal performance.

[0055] In another exemplary embodiment, the heating temperature of the sealed and vacuumed mold is 80° C. to 180° C.

[0056] In this embodiment, the mold after being pressurized within the above-mentioned pressurization pressure range is subjected to heating treatment at multiple temperatures, such as 60°C, 80°C, 100°C, 180°C, and 200°C, and the performance of the grinding blocks prepared at different temperatures is tested. It is found through testing that when the heating temperature is 60°C and 200°C, the various indicators of the prepared grinding blocks are lower than those at 80°C, 100°C, and 180°C, as shown in Table 2: Table 2 It can be seen from Table 2 that when the temperature is 80°C, 100°C and 180°C, all indicators of the grinding block are better than those at 60°C and 200°C. Therefore, this embodiment selects 80°C to 180°C as the optimal heating temperature range.

[0057] After analysis, it was found that the reason was that if the temperature was too low, the curing reaction of the binder in the premix would be slow or even incomplete, and the release rate of the volatile components would slow down, resulting in the volatile components remaining in the premix, thus affecting the quality of the grinding block. If the temperature was too high, the volatile components would evaporate too quickly, resulting in the formation of bubbles. In addition, the binder would also begin to decompose at too high a temperature, resulting in a decrease in the performance of the grinding block.

[0058] In summary, the heating temperature of 80 ℃ to 180 ℃ is a reasonable range after practical testing. Within this heating temperature range, it can ensure that the adhesive is properly cured and the bonding strength between the materials is ensured; it can also ensure that the volatile components are released at an appropriate rate to avoid volatilization too fast or too slow, thereby obtaining high-quality grinding blocks.

[0059] Furthermore, the heating temperature range of 80°C to 180°C described in this embodiment was further tested, and it was found that when the heating temperature was 150°C, the performance indicators of the prepared grinding block were all optimal, as shown in Table 3: Table 3 It can be seen from Table 3 that when the temperature is 150°C, all indicators of the grinding block are better than those at 80°C, 100°C and 180°C. Therefore, this embodiment selects 150°C as the optimal heating temperature.

[0060] After analysis, it was found that the reason is that when the heating temperature is 150 °C, the curing reaction of the adhesive can be activated to the maximum extent, thereby ensuring that the remaining materials can be most fully combined. And at this temperature, the release rate of the volatile components in the premix is ​​the most stable, neither too fast nor too slow, which can minimize the formation of bubbles. Therefore, this embodiment selects 150 °C as the optimal heating temperature, which can effectively control the release rate of volatile components while ensuring that the adhesive is fully cured, thereby obtaining a high-quality polyhedron high-temperature cast high-gloss grinding block.

[0061] Next, the present disclosure uses the aforementioned index test methods to compare the performance of the grinding block prepared by the present method embodiment with the traditional powder hot pressing grinding block. The specific comparison results are shown in Table 4: Table 4 It can be seen from Table 4 that, compared with the traditional powder hot-pressed abrasive block, the wear resistance of the abrasive block prepared by this method is improved by about 60% (from 0.05g / 1000 revolution to 0.02g / 1000 revolution); the mechanical strength is increased by about 25% (from 1200 Newtons to 1500 Newtons); the toughness is increased by about 20% (from 25 joules to 30 joules); the hardness is increased by about 9% (from 55 HR to 60 HR); and the density is increased by about 8% (from 2.5g / cubic centimeter to 2.7g / cubic centimeter).

[0062] Through the above comparison, it can be seen that the polyhedron high temperature cast high gloss abrasive block prepared by this method is superior to the traditional powder hot pressed abrasive block in terms of wear resistance, mechanical strength, toughness, hardness and density. This is mainly due to the optimization of material ratio and the improvement of preparation process, especially the precise control of vacuum degree, pressurization pressure and heating temperature, thus ensuring that the abrasive block has better performance.

[0063] Furthermore, the present disclosure also compares the polishing degree of the abrasive block prepared by the present method with that of the traditional powder hot-pressed abrasive block, which can be quantitatively analyzed by the index of surface roughness.

[0064] In this embodiment, the surface roughness of the grinding block can be measured by a profile measuring instrument. Commonly used instruments include optical interferometers, stylus profilometers, etc. Among them, the stylus profilometer is a commonly used method, which moves a stylus on the surface of the sample, records the changes of the stylus with the undulations of the surface, and then calculates the parameters of the surface roughness.

[0065] After testing, the surface roughness of the grinding block prepared by the best embodiment of the method is Ra 0.2μm, and the surface roughness of the traditional powder hot-pressed grinding block is Ra 0.4μm. The smaller the surface roughness Ra value, the smoother the surface, and vice versa. The surface roughness of the grinding block prepared by the present method is significantly lower than that of the traditional powder hot-pressed grinding block, indicating that the surface of the grinding block prepared by the present method is smoother.

[0066] In addition, it can be seen from Table 4 that the wear resistance of the traditional powder hot-pressed abrasive block is 0.05g / 1000 revolutions, while the wear resistance of the abrasive block prepared by the best embodiment of the present method is 0.02g / 1000 revolutions, which indicates that the abrasive block prepared by the present method has higher wear resistance, and thus it can be further proved that the surface roughness of the abrasive block prepared by the present method is lower.

[0067] In summary, since the wear resistance, mechanical strength, toughness, hardness and density of the abrasive block prepared by this method are better than those of the traditional powder hot-pressed abrasive block, the abrasive block can maintain better surface integrity and shape stability during use, thereby reducing surface wear and damage, and further improving the polishing brightness stability of the abrasive block. The above are only preferred embodiments of the present disclosure, and are not intended to limit the patent scope of the present disclosure. Any equivalent structure or equivalent process transformation made using the contents of the present disclosure and the drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present disclosure.

Claims

1. A polyhedral high-temperature cast high-gloss grinding block, characterized in that: The components of the grinding block include adhesive, reinforcing agent, superhard material, toughening agent and hollowing material, and the mass percentages of the adhesive, reinforcing agent, superhard material, toughening agent and hollowing material are: 5% to 15%, 1% to 10%, 70% to 80%, 1% to 5%, and 0 to 5%, respectively.

2. A method for preparing a polyhedral high-temperature cast high-gloss abrasive block, characterized in that: Preferably, the method comprises the following steps: The binder, reinforcing agent, superhard material, toughening agent and hollowing material as raw materials are suspended and stirred at room temperature and pressure according to a preset ratio to prepare a premix; The premix is ​​added into a polyhedron high temperature casting high gloss abrasive block mold, hook-shaped Velcro is covered on the surface of the premix, and then the mold is sealed and vacuumed; The sealed and vacuumed mold is pressurized and heated to obtain a polyhedron high-temperature cast high-gloss grinding block cutter head; The polyhedron high temperature cast high gloss grinding block head is bonded to the rubber spring pad and the ABS card board, and then subjected to constant pressure molding to obtain the polyhedron high temperature cast high gloss grinding block.

3. The preparation method according to claim 2, characterized in that: The adhesive includes any one of the following: glass fiber reinforced plastic resin, epoxy resin, unsaturated polyester resin, phenolic resin, polyurethane resin and silicone resin.

4. The preparation method according to claim 2, characterized in that: The reinforcing agent includes any one of the following: calcium sulfate whisker, silicon carbide whisker, silicate lime whisker, silicon nitride whisker and aluminum oxide whisker.

5. The preparation method according to claim 2, characterized in that: The superhard material includes any one of the following: artificial diamond, silicon carbide, aluminum oxide, cubic boron nitride and zirconium dioxide.

6. The preparation method according to claim 2, characterized in that: The pore-forming material includes any one of the following: sodium chloride, anhydrous sodium sulfate, sodium sulfate, sucrose pellet core and baking soda.

7. The preparation method according to claim 2, wherein: The raw materials also include polishing powder.

8. The preparation method according to claim 2, wherein: The mold was evacuated to -0.01 MPa to -0.1 MPa.

9. The method according to claim 2, wherein: The pressure applied to the sealed and evacuated mold is 1000 MPa to 1900 MPa.

10. The method according to claim 2, wherein: The heating temperature of the sealed and evacuated mold is 80°C to 180°C.

Citation Information

Patent Citations

  • Elastic grinding block tool bit for glazed brick and preparation method of elastic grinding block for glazed brick

    CN117020977A

  • Elastic grinding block as well as preparation method and application thereof

    CN117984240A

  • Composite binding agent grinding wheel and preparation method thereof

    US20230042029A1